Bulgarian Composers of St. John Chrysostome’s Liturgy - Malinov, Stoyan (Forum Theologicum Sardicense, 2025)
Stoyan Malinov, Bulgarian Composers of St. John Chrysostome’s Liturgy. This article aims to present the original church music in Bulgarian since its Liberation (1878) to the present day. The central point of interest for the composers is the liturgy of St. John Chrysostom. The authors under consideration have constructed their musical creation on all pars of the Holy Liturgy. The period under consideration shows the different charac- teristics of the evolution of the ecclesial chant tradition and heritage. Three general tendencies emerge in the aspiration of the authors to create of new church chanting creations based on national traditions: on the one hand – “Bulgarian chant” (bolgarskii raspev) and on the other – the “Easter church chants”, and, finally, the original Bulgarian authors’ new creations.